2004
DOI: 10.1111/j.0013-9580.2004.28903.x
|View full text |Cite
|
Sign up to set email alerts
|

A Dissociation between Implicit and Explicit Verbal Memory in Left Temporal Lobe Epilepsy

Abstract: Summary: Purpose: Temporal lobe epilepsy patients are well known to present deficits on explicit verbal memory procedures (e.g., recall, recognition). The integrity of implicit memory procedures in these patients is not established. Previous studies in this area used implicit memory measures contaminated by the effects of explicit memory.Methods: We examined the integrity of verbal implicit and explicit memory in left temporal lobe epilepsy (LTLE) patients and hypothesized that a clear dissociation in performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…Our findings confirm previous studies showing that implicit and explicit recognition processes are underpinned by different information processing systems [2]. It has been proposed that the hippocampus is important to explicit memory mechanism, which requires intentional and conscious recollection [8]. They also reported that the medial temporal lobe is involved in implicit memory measures contaminated by the effect of explicit memory.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings confirm previous studies showing that implicit and explicit recognition processes are underpinned by different information processing systems [2]. It has been proposed that the hippocampus is important to explicit memory mechanism, which requires intentional and conscious recollection [8]. They also reported that the medial temporal lobe is involved in implicit memory measures contaminated by the effect of explicit memory.…”
Section: Discussionsupporting
confidence: 91%
“…Priming effects concern implicit, unconscious memory abilities of past experiences, which have an indirect influence on future behavior 16 . The assessment of such effects is done by means of indirect tests, that is, those which involve motor or cognitive activities related to a learning event, but in which the instructions do not directly refer to that.…”
Section: The Semantic Priming Paradigmmentioning
confidence: 99%
“…In addition to the well-addressed impairment of cognitive functions such as memory [15,47] and language [1], functional alteration of perceptions in mTLE are often reported. A series of behavioral and electrophysiological studies by Grant et al and other authors revealed that somatosensory [4,18,22,25] and auditory [16,24] perceptions are impaired.…”
Section: Introductionmentioning
confidence: 99%
“…With better temporal and spatial resolutions, BOLD-fMRI has been widely used for investigation of epilepsy [21]. However, the current fMRI studies of mTLE have been limited to the evaluation of memory and language deficits [1,15,47] or detection of abnormal epileptic activations in the brain [2,33,34]; changes in the perceptual systems have seldom or not yet specifically been addressed in patients with mTLE.…”
Section: Introductionmentioning
confidence: 99%